Clinical researchStudy of T-cell stimulation and cytokine release induced by Staphylococcal enterotoxin type B and monophosphoryl lipid A - Fooladi, Abbas Ali; Sattari, Morteza; Nourani, Mohammad R. (Archives of Medical Science, 2009)
Introduction: In vitro exposure of T cells to SEB is known to activate T cells in a subset restricted manner based on b-chain variable region (Vb) gene expression. Monophosphoryl lipid (MPL) is an adjuvant derived from a lipopolysaccharide obtained from gram negative bacteria. This study examined the ability of Staphylococcal enterotoxin type B (SEB), MPL and SEB + MPL to activate T cells in vitro. Material and methods: Lymphocyte cells derived from lymph node Balb/c mice were exposed to series of doses of SEB, MPL and SEB + MPL (1.10, 102, 103 and 104 ng/µl) in order to evaluate the magnitude of proliferation and activation of lymphocyte cells on the basis of a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Results: Results of this investigation showed that the optimal concentration of SEB + MPL for activation of lymphocyte cells was 100 ng/µl (p < 0.05). Additionally, using Hoechst staining, we studied the ability of SEB, MPL and SEB + MPL to induce apoptosis. The results indicated no significant difference between the treatment and negative control groups. We concluded that 100 ng/µl of SEB, MPL and SEB + MPL did not generate apoptosis; they only induced the activation of lymphocyte cells. We also clarified that the combination of SEB and MPL can cause more stimulation and proliferation of mouse lymphocyte cells than any individual component or the negative control. Conclusions: Our data suggest that MPL is a suitable adjuvant that probably leads to more sustained effect of SEB. Because the results of our cytokine assay indicate that the level of IFN-g compared with IL-4, SEB + MPL could be a candidate for tumor therapy.